The Effect of Work Facilities and Incentives on Employee Performance Mediated by Work Discipline at The Regional Public Drinking Water Company Tirta Mayang, Jambi City - Asbiliyah Asbiliyah; M. Zahari; Osrita Hapsara (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the effect of work facilities and incentives on employee performance, with work discipline as a mediating variable at the Regional Drinking Water Company (Perumdam) Tirta Mayang in Jambi City. Employee performance is a key factor in improving the quality of public services, particularly in the clean water supply sector. This study used a quantitative approach with a survey method. The study population was all 153 employees of Perumdam Tirta Mayang in Jambi City. The sample size was determined using the Slovin formula with a tolerance of 7.5%, resulting in a sample size of 111 respondents. Data analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that work facilities and incentives had a positive and significant effect on work discipline. Work facilities and incentives also had a positive and significant effect on employee performance. Furthermore, work discipline had a positive and significant effect on employee performance and mediated the effect of work facilities and incentives on employee performance. These findings emphasize the importance of providing adequate work facilities and a fair incentive system to improve employee discipline and performance.